Effectiveness of group counseling treatment on marital adjustment, parenting stress, and depression among parents of autistic children in Jordan - Alhorany, Ahmed Kamel (2012)
Autism is a prevalent developmental disorder with prominent impairments in social reciprocity, language impairment and restricted repetitive behaviors or interest. It disturbs the autistic individuals and the people involved with them. Particularly, parents of autistic children have to encounter difficulties and challenges triggered by their children. They experience higher risks of marital discord, parenting stress, and depression. Although group counseling is known to be cost- effective treatment and has been recommended for parents of autistic children, literature remains scarce for Jordanians. Therefore, the main purpose of this study is to examine the effectiveness of group counseling treatment (with structural family therapy and cognitive behavioral therapy) on marital adjustment, parenting stress and depression in parents of autistic children in the city of Irbid, Jordan. The study adopted a randomize control pretest-posttest design with one month follow up. Participants consisted of 30 males and 30 females were randomly assigned to an experimental group (group counseling treatment) and to a control group (no treatment). The instruments employed were the Dyadic Adjustment scale (DAS) to measure marital adjustment, the Parenting Stress Scale (PSS) to measure parenting stress and the Beck Depression Inventory (BDI) to measure depression. The collected data were coded and then analyzed using the Statistical Package for Social Sciences (SPSS) software version 16. Results of repeated-measures ANOVA showed that there were significant differences in the marital adjustment, parenting stress, and depression scores between the experimental and control group over time but there were partial significant interaction effects with gender. The results suggested 48% significant improvement in marital adjustment, 38 % and 50% of reductions in parenting stress and depression respectively. Depression continued to decrease even after the treatment was over. Furthermore, at significant level !=.01, the results of MANOVA revealed that the mean scores of marital adjustment subdimensions (cohesion, consensus, and satisfaction) for the experimental group were significantly higher than those of the control group, In conclusion, the findings indicated that the group counseling treatment was effective in improving the marital adjustment as well as in reducing parenting stress and depression in parents of autistic children in the city of Irbid, Jordan. Theoretically, this study supports the amalgamation of key concepts of structural family therapy and cognitive behavior therapy in a form of group counseling treatment for Jordanian parents. Findings on marital adjustment sub-dimensions strengthen the notion that Arab families are enmeshed with high regard to cohesion and consensus. Practically, the findings of the study have implications for mental health centers and for marital and family therapists who provide treatment for parents of autistic children. Future studies of different populations may be needed to replicate the findings and for generalization.